The practices of digital comic media based on the PBL model in elementary school - Mifthahul Jannah; Reinita Reinita; Ferdian Admil Sandika (Jurnal Inovasi Teknologi Pendidikan, 2023)
Lack of use of media that is interesting, fun, and easy for students to understand makes students have difficulty understanding the material and often feel bored and lack motivation to learn. The requirement for learning media tailored to studentsâ€™ interests spurred this studyâ€™s development of useful PBL-based digital comic learning media in Class IV Elementary Schools. Comics in learning follow studentsâ€™ thinking levels, especially elementary school students. Techniques are used sequentially to make communication and interaction between teachers and students more effective in the learning and teaching process. A teacher's success in the learning process is when students can understand the material conveyed by the teacher to shape students' character through learning media. This study uses the ADDIE development methodology for analysis, design, development, implementation, and evaluation. Students at SDN 32 Andalas in the fourth grade participated in this study. 95.8% of teachers responded to the teacher response survey, and 98.8% of students responded to the student response survey, both of which were â€œvery practical.â€ Thus, digital comic learning media in PKN learning in class IV of elementary school has been declared practical.